Economic development what everyone needs to know - Giugale, Marcelo M. (Oxford University Press, 2014)
"The practice of economic development has undergone significant transformation over the past decade, due to globalization and democratization. While beneficiaries previously held little sway in the way international economic institutions delegated funds for projects, today it would be difficult-if not impossible-for the average government or for the average multilateral organization to build a road, reform an education curriculum, or sign a mining concession without, at a minimum, a process of consultation with those affected. This change has created a greater demand for development knowledge. Economic Development: What Everyone Needs to Know provides a clear and concise introduction to the development problems that policy-makers, professionals, development agencies, NGOs, charities, and private citizens face. Beginning with the basic concepts that inform the practice of development, this wide-ranging book addresses the major challenges that shape the field, highlighting the doubts, trade-offs, and dilemmas. Drawing on his more than twenty-five years of experience working in development in the Middle East, Eastern Europe, Central Asia, Latin America and Africa, Marcelo Giugale illustrates his chapters with real-life examples from all over the globe. He looks at a host of topics including the reasons why seemingly obvious reforms never happen, power dynamics between governments and beneficiaries, government corruption, state violence, natural resources, globalization and trade, anticipating global crises, measuring equity, ending poverty, the "new" poor, gender, indigenous peoples, children, health care, food prices, and technology. While development is a complex area in which there are no definitive answers, Giugale highlights the very real challenges that face the profession now and will continue to face development practitioners in the years to come"--Provided by publisher.